2021
DOI: 10.1371/journal.pone.0249421
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function analysis in COVID-19: A retrospective study from a single center

Abstract: Background and objective Coronavirus disease 2019 (COVID-19) is an on-going epidemic with a multitude of long-ranging effects on the physiological balance of the human body. It can cause several effects on thyroid functions as well. We aimed to assess the lasting sequelae of COVID-19 on thyroid hormone and the clinical course of the disease as a result. Methods Out of 76 patients, 48 patients of COVID-19 positive and 28 patients of COVID-19 negative polymerase chain reaction (PCR) were assessed for thyroid f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 19 publications
(23 reference statements)
4
38
0
Order By: Relevance
“…ESS related to COVID-19 was seen in 16–48% of cases in different reports [ 3 , 4 , 7 12 ]. However, these studies have several limitations, such as small sample size [ 3 , 7 , 10 , 11 , 13 ], drug interferences [ 3 , 6 ], and limited test panel [ 3 , 5 , 6 , 8 ]. Only two studies had evaluated thyroid autoimmunity [ 9 , 12 ], and prior thyroid function tests were assessed only in another [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ESS related to COVID-19 was seen in 16–48% of cases in different reports [ 3 , 4 , 7 12 ]. However, these studies have several limitations, such as small sample size [ 3 , 7 , 10 , 11 , 13 ], drug interferences [ 3 , 6 ], and limited test panel [ 3 , 5 , 6 , 8 ]. Only two studies had evaluated thyroid autoimmunity [ 9 , 12 ], and prior thyroid function tests were assessed only in another [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies on COVID-19 have shown thyroid function abnormalities that were interpreted as a euthyroid sick syndrome (ESS) [ 3 13 ] ( Table 1 ) or thyrotoxicosis associated with destructive thyroiditis [ 5 , 6 ]. However, several limitations such as small study population, incomplete evaluation of thyroid function tests, no control group, and drug interference exist in those studies [ 3 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mentioned study suggested that changes in serum TSH and TT3 levels may be important manifestations of the courses of COVID‐19 pneumonia. 7 After clinical recovery, these derangements in serum thyroid hormone may be permanent. Based on previous studies conducted on SARS‐CoV, 6.7% of patients developed hypothyroidism, and the majority of these patients (75%) had a central hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…However, changes in thyroid function were reported during the previous SARS-CoV outbreak [59,60]. A study carried out during the 2003 SARS outbreak found significantly reduced serum T3 and T4 concentrations in patients with SARS compared to healthy controls in both the progression and recovery stages of the disease, with low T3 concentrations associated with disease severity [59]. Leow et al evaluated 61 SARS-CoV survivors three months after recovery, looking for hormonal abnormalities and found that four (6.7%) of the patients had developed biochemical hypothyroidism.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Evaluation of thyroid function for COVID-19 is not part of the WHO's guidelines for clinical management [58]. However, changes in thyroid function were reported during the previous SARS-CoV outbreak [59,60]. A study carried out during the 2003 SARS outbreak found significantly reduced serum T3 and T4 concentrations in patients with SARS compared to healthy controls in both the progression and recovery stages of the disease, with low T3 concentrations associated with disease severity [59].…”
Section: Clinical Manifestationsmentioning
confidence: 99%